Keteraturan dan Ketidakteraturan Isotopi pada Simbol dalam Puisi Karya Stéphane Mallarmé - Rahma Zahra Putri Yudistira; Dadang Sunendar; Dudung Gumilar (JURNALISTRENDI : JURNAL LINGUISTIK, SASTRA, DAN PENDIDIKAN, 2026)
This study analyzes and describes how isotopic regularity and irregularity manifest through symbols in three symbolic poems by Stéphane Mallarmé titled Brise Marine (1865), Les Soupirs (1864), and Éventail (1884). These three poems share thematic elements centered on absence, silence, and the search for spiritual meaning. Greimas’s theory of isotopy serves as the foundation for analyzing semantic consistency or the repetition of meaning within the text. This qualitative descriptive study with structural-semiotic analysis focuses on identifying isotopies—both regular and deviant—to uncover the symbolic meanings within the works. The research involves structural analysis to identify coherent isotopies, interpret symbols exhibiting irregularity to uncover deeper meanings, and track the repetition of semantic units in determining regularity and irregularity within the poems. The results indicate that 61 symbols from the three poems contain a clash between the regularity and irregularity of isotopy. The groups of isotopic regularity identified include: intellectual isotopy, social isotopy, existential isotopy, inner isotopy, isotopy of beauty and purity, seasonal isotopy, isotopy of hope, isotopy of imagination, natural isotopy, emotional isotopy, and isotopy of authority. Meanwhile, the isotopic irregularities identified include: the isotopy of the urge to escape, the isotopy of the journey, the isotopy of failure or destruction, aimless movement, the isotopy of solitude or emptiness, suffering, exhaustion, the isotopy of the boundaries between reality and imagination, the isotopy of aimless romance, feelings of being held back, and tempting desires. Keywords: isotopy; regularity; irregularity; poetry; symbolism